Use of grazing according to the kidding period to improve the sustainability of dairy goat farms in France - Caillat H.; Duprat A.; Bruneteau E.; Ranger B.; Paraud C.; Bossis N.; Jost J. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
France is the largest producer of goat’s milk in Europe with about 550 millions of liters collected. Since 2000, goat farms have moved towards intensive farming, largely increasing their need in purchased inputs, particularly feeds. To increase productivity, grazing has been gradually abandoned and indoor breeding has been developed. Resorting again to grazing could be a solution for improving the sustainability of goat farms, with a better control of feeding costs and a greater security of systems. In 2012, a system-experiment in Western France was designed at Inra to determine if this low-input solution would lead to high-performance farming systems. The system-experiment aimed at evaluating 2 independent farms of 60 Alpine goats differing in kidding period (February, GF or September, GS). Gastrointestinal parasitism was controlled every month by measuring strongyles’ faecal egg excretion on faecal group samples. Between 2015-2018, annual mean grazing duration and average milk yield were higher for the GF farm (+ 37 days.year-1, +25%; + 71 L.goat-1.year-1, +11%). However, the amount of concentrates and dehydrated feed was higher for GS farm (+14 kg.goat-1.year-1) despite a high proportion of herbage in the ration (68 ± 4%). Purchased feed costs were generally low (147 ±34€ per 1000 L), and higher for the GS farm (+ 47€ per 1000 L). This higher purchase cost had no consequences because the price of milk was higher for the GS farm (+ 56€ per 1000 L). Annual mean flock excretions of strongyles were low (178 ±233 eggs per gram of faeces), but varied highly after the period of the year. Increase in grazing of high value grasslands seems thus to be an interesting option to improve the sustainability of dairy goat systems in France, whatever the kidding period.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)